Improving quality of teaching and child development: A randomised controlled trial of the leadership for learning intervention in preschools - Siraj, Iram; Melhuish, Edward; Howard, Steven J.; Neilsen-Hewett, Cathrine; Kingston, Denise; De Rosnay, Marc; Huang, Runke; Gardiner, Julian; Luu, Betty (Frontiers in Psychology, 2023)
Substantial research indicates that high quality early childhood education and care (ECEC) confers a wide range of benefits for children, yet quality in ECEC remains inconsistent. Given the variability in training and qualifications, one strategy for improving ECEC quality is in-service professional development (PD). The current study evaluated an evidence-based in-service PD programme, Leadership for Learning, via a cluster randomised controlled trial involving 83 ECEC services and 1,346 children in their final year of pre-school. Results indicated significant improvements in teaching quality across treatment centres and child development outcomes in language, numeracy and social-emotional development. This provides strong support for making evidence-informed PD routinely available for ECEC practitioners.